Contemporary Management of Out-of-hospital Cardiac Arrest in the Cardiac Catheterisation Laboratory: Current Status and Future Directions - Nilesh Pareek; Peter Kordis; Ian Webb; Marko Noc; Philip MacCarthy; Jonathan Byrne (Interventional Cardiology: Reviews, Research, Resources)
Out-of-hospital cardiac arrest (OHCA) is an important cause of mortality and morbidity in developed countries and remains an important public health burden. A primary cardiac aetiology is common in OHCA patients, and so patients are increasingly brought to specialist cardiac centres for consideration of coronary angiography, percutaneous coronary intervention and mechanical circulatory support. This article focuses on the management of OHCA in the cardiac catheterisation laboratory. In particular, it addresses conveyance of the OHCA patient direct to a specialist centre, the role of targeted temperature management, pharmacological considerations, provision of early coronary angiography and mechanical circulatory support.